Monitoring South-South Cooperation (October 2018 to September 2019) - Surasky, Javier (Revista Española de Desarrollo y Cooperación, 2023)
This section presentation is unusual since it covers a full year of events in the South-South Cooperation. It also includes a chapter related to the Second United Nations High-Level Conference on South-South Cooperation, met in Buenos Aires in early 2019 to commemorate the 40th anniversary of the adoption of the Plan of Action of Buenos Aires to Promote and Implement Technical Cooperation among Developing Countries (BAPA). Besides, we include a brief final section on SSC and the 2030 Agenda for Sustainable Development.